The Effect of Shoot Cuttings and Vermiwash Concentration on Orchid Growth (Onchidium sphacelatum Lindl.) Aeroponically - Ibrahim; Santoso, Untung; Zainudin, Agus; Pangestika, Padhina (Universitas Muhammadiyah Malang, 2024)
The Oncidium sphacelatum orchid, commonly propagated vegetatively through pseudobulb separation, presents opportunities for further research into propagation methods and organic fertilizer application. This study, conducted in Batu City, aimed to explore the interaction between vermiwash concentration and shoot number on aeroponically cultivated Orchid sphacelatum Lind cuttings, as well as individual treatment effects. Employing a factorial RKLT design with shoot number (one or two) and vermiwash concentration (100, 200, or 300 ml/L) as factors, the study evaluated plant height, leaf count, stem length, shoot length, root count, and root length as variables. Data analysis involved ANOVA and BNJ tests. Results revealed that cuttings with two shoots and a 200 ml/L vermiwash concentration promoted optimal leaf growth. The number of shoots influenced shoot length, with two shoots demonstrating superior growth compared to single shoot cuttings. Interestingly, vermiwash concentration did not significantly impact shoot growth parameters, indicating that its effects may be limited in this context. This study sheds light on the potential benefits of using vermiwash in orchid cultivation, particularly in enhancing leaf growth when combined with multiple shoot cuttings. However, further investigation is needed to understand the nuanced effects of vermiwash on other growth aspects and its interaction with different propagation methods.Overall, the findings contribute to the optimization of orchid propagation techniques, providing valuable insights for orchid growers seeking to enhance plant growth and productivity sustainably. Further research could delve deeper into the mechanisms underlying the observed effects and explore additional variables to refine cultivation practices for Oncidium sphacelatum orchids.